2015
DOI: 10.1123/jsep.2014-0331
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Task Self-Efficacy and Emotion Across Competitive Performances in Golf

Abstract: This research aimed to investigate (a) the effect of golfers' perceptions of coach motivation efficacy on golfers' precompetition task self-efficacy, (b) the effect of performance on pre-to-postround changes in self-efficacy, (c) the effect of pre-to-postround changes in self-efficacy on pre-to-postround changes in affect and emotion, and (d) whether any effects of performance on pre-to-postcompetition changes in affect and emotion were mediated by pre-to-postcompetition changes in self-efficacy. In Study 1, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…For instance, Feltz et al (1999) found higher levels of player satisfaction and higher winning percentages for high-CE coaches compared to low-CE coaches. Further, and found athletes' perceptions of their coach's competency were predictive of increased satisfaction with their coach, and Boardley et al ( , 2015 showed heightened perceptions of coach's motivation effectiveness positively predicted athletes' task self-efficacy in rugby and golf. Therefore, consistent with the CE model, research has supported numerous outcomes of CE.…”
Section: Summary Of Key Findingsmentioning
confidence: 95%
See 2 more Smart Citations
“…For instance, Feltz et al (1999) found higher levels of player satisfaction and higher winning percentages for high-CE coaches compared to low-CE coaches. Further, and found athletes' perceptions of their coach's competency were predictive of increased satisfaction with their coach, and Boardley et al ( , 2015 showed heightened perceptions of coach's motivation effectiveness positively predicted athletes' task self-efficacy in rugby and golf. Therefore, consistent with the CE model, research has supported numerous outcomes of CE.…”
Section: Summary Of Key Findingsmentioning
confidence: 95%
“…Finally, perceptions of coach effectiveness represent 'the extent to which coaches can implement their knowledge and skills to positively affect the learning and performance of their athletes' (Boardley, Kavussanu, & Ring, (2008, p.271). Importantly, factorial analyses have shown support for the original dimensional structure from the CE model in such perceptions (Boardley et al, 2008;Boardley, Jackson, & Simmons, 2015;. Research investigating athletes' perceptions of their coach is reviewed next, with studies grouped by the specific perception assessed.…”
Section: Athletes' Perceptions Of Their Coachmentioning
confidence: 99%
See 1 more Smart Citation
“…An additional role strain can be experienced by the psychological impact of retirement and job loss. In such a case, a CEO may begin to more deeply consider the alternatives to leaving that were not taken (Obodaru, 2012 ). It has been acknowledged that how a person frames their departure has a direct impact on their emotional wellbeing (Lazarus and Folkman, 1984 ; Latack et al, 1995 ; McFadyen, 1995 ; Ashforth, 2001 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…We hope to add to the growing understanding of the connections between role transition and identity (Ibarra and Barbulescu, 2010 ; Obodaru, 2012 ), but we also seek to broaden the discussion in the literature by looking at identity and role transition with a specific career role (owner CEOs) and career decision (voluntary transition). Thus, this study focuses on a work transition that is different from those traditionally studied.…”
Section: Introductionmentioning
confidence: 99%